2016
DOI: 10.3171/2016.2.focus161
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced brain injury: low-hanging fruit for neuroregeneration

Abstract: Brain radiation is a fundamental tool in neurooncology to improve local tumor control, but it leads to profound and progressive impairments in cognitive function. Increased attention to quality of life in neurooncology has accelerated efforts to understand and ameliorate radiation-induced cognitive sequelae. Such progress has coincided with a new understanding of the role of CNS progenitor cell populations in normal cognition and in their potential utility for the treatment of neurological diseases. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 97 publications
1
30
0
2
Order By: Relevance
“…We observed a similar pattern in myelin density changes in irradiated rats as in controls, although there appeared to be a non-significant tendency toward an increase in myelin density 3 months after radiation therapy, as compared to day 60. In line with our data, previous studies suggested that demyelination after 25-Gy WBRT in rodents is a process that mainly occurs in the acute phase (Burns et al 2016), with myelin density recovering to normal levels after around 3-6 months (Panagiotakos et al 2007;Fu et al 2017). This recovery is hypothesized to occur mainly due to the capacity of oligodendrocyte progenitor cells to migrate to the sites of myelin damage and remyelinate the injured white matter tracts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed a similar pattern in myelin density changes in irradiated rats as in controls, although there appeared to be a non-significant tendency toward an increase in myelin density 3 months after radiation therapy, as compared to day 60. In line with our data, previous studies suggested that demyelination after 25-Gy WBRT in rodents is a process that mainly occurs in the acute phase (Burns et al 2016), with myelin density recovering to normal levels after around 3-6 months (Panagiotakos et al 2007;Fu et al 2017). This recovery is hypothesized to occur mainly due to the capacity of oligodendrocyte progenitor cells to migrate to the sites of myelin damage and remyelinate the injured white matter tracts.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we used PET to assess the late-delayed changes in white matter after WBRT, using 11 C-MeDAS as a tracer for myelin density and 18 F-FDG as a tracer for brain glucose metabolism. Demyelination is directly related to the white matter damage after WBRT (Burns et al 2016;Torrens et al 2016;Li et al 2018), whereas glucose metabolism could be considered a surrogate marker for neurodegeneration. The tracer 11 C-MeDAS has previously successfully been used for PET imaging of myelin loss and regeneration in various rodent models for multiple sclerosis (Wu et al 2010(Wu et al , 2013de Paula Faria et al 2014a, 2014b, 2014cFaria et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the more radiation-like polarization state of aged microglia contributes to such poorer outcomes remains unknown. However, given the recurrent theme of chronic inflammation, in GBM, radiation, aging, and neurodegeneration, efforts to modulate the inflammatory microenvironment of both primary and recurrent GBM are of broad interest to attenuate tumorigenesis and enhance cognitive outcomes following radiation ( 172 , 173 ). Given the differences in the neuroinflammatory phenotype of rodents and humans, mechanistic studies specifically interrogating human disease will be paramount ( 174 ).…”
Section: Effects Of Radiation Therapy On the Gbm Microenvironmentmentioning
confidence: 99%
“…Cellular damage is not limited to neurons, but extends to glial cells, with oligodendrocytes being particularly vulnerable. Oligodendrocytes have high metabolic demands and mitochondrial content, making them sensitive to the oxidative stress caused by radiation [14, 15]. Damage to oligodendrocyte progenitor cells and fully differentiated oligodendrocytes with subsequent white matter necrosis due to axonal demyelination and degradation has been observed [3, 14, 16, 17].…”
Section: Introductionmentioning
confidence: 99%